Trend of cancer mortality rates and glyphosate consumption in Brazil (Research, Society and Development, 2020)
Incluir o resumo em inglês. This study presents results of the trend analysis of standard cancer mortality rates (TPMC) and glyphosate consumption in Brazil from 1990 to 2016. The joinpoint TPMC method and glyphosate consumption were used. Mortality data were obtained from the Mortality Information System and data on glyphosate consumption was estimated by type of agricultural crop. TPMC went from 64.7 to 103.6 per 100,000 inhabitants and the consumption of glyphosate from 74 to 203 million liters in 27 years. For males, colon and rectal cancer showed an increasing trend with the average annual percentage variation (AAPC) of 7.3% (p